2017
DOI: 10.1002/adom.201700368
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Light at the Nanoscale: Structural Color Filters and Broadband Perfect Absorbers

Abstract: Recent advances in fabrication and processing methods have spurred many breakthroughs in the field of nanostructures that provide novel ways of manipulating light interaction on a well controllable manner, thereby enabling a wide variety of innovative applications. Structural colors have shown great promise as an alternative for existing colorant‐based filters due to their noticeable advantages, which open up diverse potential applications such as energy‐efficient displays, ultrahigh‐resolution imaging, ultrah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(126 citation statements)
references
References 235 publications
(281 reference statements)
0
126
0
Order By: Relevance
“…There is now a considerable body of work investigating plasmonic structural color and we refer the interested reader to several excellent recent review articles . Here we focus on coloration produced by NPA achieved using plasmonic effects.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is now a considerable body of work investigating plasmonic structural color and we refer the interested reader to several excellent recent review articles . Here we focus on coloration produced by NPA achieved using plasmonic effects.…”
Section: Applicationsmentioning
confidence: 99%
“…Here we focus on coloration produced by NPA achieved using plasmonic effects. A previous review of strong absorption and coloration can be found in Ji et al…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between visible light and nanostructures can develop colors in the absence of any chemical pigments or dyes . Periodic nanostructures with spatial modulation of refractive index possess photonic bandgap (PBG), which produces a color through the selective reflection of light at the PBG .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, structural color filters relying on the phenomenon of interference resulting from material structure represent an alternative approach . Examples of structural‐based color filters include Fabry–Pérot interferometers, waveguide grating structures, and plasmonic resonators . A structural‐based approach possesses a number of advantages like high tolerance to heat, resistance to photodegradation, and long‐term stability.…”
mentioning
confidence: 99%